Cost-effectiveness analysis of interventions to increase physical activity in hypertensive patients - Espinosa-Ortega, Gisela; Heredia-Pi, Ileana Beatriz; Garnelo-Bibiano, Nicéforo; Gallegos-Carrillo, Katia (Horizonte Sanitario, 2022)
Objective: To perform a cost-effectiveness analysis (CEA) of two programs designed to increase the physical activity (PA) of hypertensive patients at the primary-care level: the first based on the Reference Scheme (RS) and the second on the Brief Counseling (BC) approach, both within the context of a Mexican social security institution: The Mexican Social Security Institute (IMSS).Material and Methods: A CEA was undertaken from the perspective of service providers, with a time horizon of 24 weeks. Effectiveness was estimated in two ways: an increase in the minutes of moderate-vigorous PA (MVPA) and the percentage of patients engaging in ≥150 weekly minutes of MVPA at the end of each program.Results: RS patients performed 8.1 additional minutes of PA (week 24 = 169.29 minutes; week zero = 161.23). RS program proved approximately 1% more expensive and more effective and had an incremental cost-effectiveness ratio of 299 US$ per increased percentage point of patients engaging in ≥150 weekly minutes of MVPA at the end of each program. The sensitivity analysis yielded an up to 56% probability that the RS program would be cost-effective in increasing the percentage of patients performing the targeted MVPA per week.Conclusions: Our results indicate that in the context of a social security institution such as the IMSS, it is not cost-effective to implement an RS-based program to increase physical activity levels in hypertensive patients. Further evidence is required on the cost-effectiveness of both programs regarding other effectiveness measures such as biochemical and physical condition parameters, as well as to other types of population, given that this was the first CEA of PA programs in Mexico.Keywords: Physical activity; Arterial pressure; Cost and cost analysis; Adults.